Fair play [large type] : a novel - Gist, Deeanne (Center Point Large Print, 2014)
There is an immediate attraction when lady doctor Billy Jack Tate and a Texas Ranger Hunter Scott meet at the 1893 Chicago World's Fair, but when the Fair is over, the conservative lawman and the progressive doctor face difficult choices.